Treatment of palm oil mill secondary effluent (POMSE) using ultrafiltration and nanofiltration membranes - Ramlee, Normarina; Ali, Nurmursalina; Misdan, Nurasyikin; Hairom, Nur Hanis Hayati; Madon, Rais Hanizam (Penerbit UTHM, 2020)
Malaysian palm oil industry has grown rapidly over the last few decades, to becoming the world’s largest producer and exporter of palm oil. This success story however, comes with a greater challenge and equally required more sacrifices in order to maintain the tempo. In the year of 2004, it has been recorded that 26.7 million tons of solid biomass and approximately a 30 million tons of palm oil mill effluent (POME) were generated from 381 palm oil mills in Malaysia [1]. Although different kind of wastes are generated in the palm oil mills, the perceived harmful waste among all the waste generated is the palm oil mill effluent (POME) due to its associated harm if discharged into the environment untreated [2]. POME is a colloidal suspension originating from mixture of sterilizer condensate, separator sludge and hydro cyclone wastewater in a ratio of 9:15:1 respectively [3]. It is a brownish colored, thick liquid that is containing high amount of oil, solids, and grease with high Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD) values. Table 15.1 describes the characteristic of POME obtained from Malaysian Palm Oil Board.